The transcriptomics profiling of blood CD4 and CD8 T-cells in narcolepsy type I - Khajavi, Leila; Nguyen, Xuan-Hung; Queriault, Clémence; Chabod, Marianne; Barateau, Lucie; Dauvilliers, Yves; Zytnicki, Matthias; Liblau, Roland (Frontiers in Immunology, 2023)
Background Narcolepsy Type I (NT1) is a rare, life-long sleep disorder arising as a consequence of the extensive destruction of orexin-producing hypothalamic neurons. The mechanisms involved in the destruction of orexin neurons are not yet elucidated but the association of narcolepsy with environmental triggers and genetic susceptibility (strong association with the HLA, TCRs and other immunologically-relevant loci) implicates an immuno-pathological process. Several studies in animal models and on human samples have suggested that T-cells are the main pathogenic culprits.Methods RNA sequencing was performed on four CD4 and CD8 T-cell subsets (naive, effector, effector memory and central memory) sorted by flow cytometry from peripheral blood mononuclear cells (PBMCs) of NT1 patients and HLA-matched healthy donors as well as (ageand sex-) matched individuals suffering from other sleep disorders (OSD). The RNAseq analysis was conducted by comparing the transcriptome of NT1 patients to that of healthy donors and other sleep disorder patients (collectively referred to as the non-narcolepsy controls) in order to identify narcolepsy-specific genes and pathways.We determined narcolepsy-specific differentially expressed genes, several of which are involved in tubulin arrangement found in CD4 (TBCB, CCT5, EML4, TPGS1, TPGS2) and CD8 (TTLL7) T cell subsets, which play a role in the immune synapse formation and TCR signaling. Furthermore, we identified genes (GZMB, LTB in CD4 and NLRP3, TRADD, IL6, CXCR1, FOXO3, FOXP3 in CD8) and pathways involved in various aspects of inflammation and inflammatory response. More specifically, the inflammatory profile was identified in the "naive" subset of CD4 and CD8 T-cell.We identified NT1-specific differentially expressed genes, providing a cell-type and subset specific catalog describing their functions in T-cells as well as their potential involvement in NT1. Several genes and pathways identified are involved in the formation of the immune synapse and TCR activation as well as inflammation and the inflammatory response.An inflammatory transcriptomic profile was detected in both "naive" CD4 and CD8 T-cell subsets suggesting their possible involvement in the development or progression of the narcoleptic process.